Comparison of Effectiveness of Insulin Glargine in Combination with Oral Hypoglycemic Agents Versus Continued Premixed Insulin in Indian Type II Diabetes Patients: Randomized Controlled Trial - Verma, Akankchha; V, Aditya; B S, Girish; Nagaraju, Kiran (Indian Journal of Pharmacy Practice)
Background and Objectives: The development of novel insulin analogs and the availability of glucose-lowering medications revolutionized the diabetes therapy protocol. The aim was to compare the efficacy and therapeutic outcome of daily insulin glargine alongside oral hypoglycemic agents and premixed human insulin in Type II diabetes priorly receiving conventional insulin therapy. Materials and Methods: This was a sixteen-week, single center, parallel randomized controlled trial. The study included participants with Type II DM who had poor glycemic control and were currently on premixed human insulin. The patients were randomized into three groups, where A received insulin glargine, B received insulin glargine, glimepiride and metformin and C were instructed to continue their previous treatment with addition of premixed insulin. The blood was collected to measure the therapeutic efficacy and all adverse events were recorded. Results: The study comprised of 185 patients and HbA1c dropped by 0.63%, 0.73% and 0.53% in group A, B and C respectively, whereas intergroup analysis did not show statistical significance. There was a significant reduction in mean fasting blood glucose levels from baseline to endpoint in every group (p=0.003; 0.014; 0.036). There were no notable significant adverse events occurred in any of the groups. Conclusion: Insulin glargine combined with glimepiride alone or with metformin serves as an efficient alternative therapy for individuals with Type II Diabetes Mellitus who failed to achieve adequate management on prior ongoing therapy with premixed insulin.
Keywords: Insulin Glargine; Diabetes Mellitus; Oral Hypoglycemic Agents; Combination Therapy